Actomyosin, vimentin and LINC complex pull on osteosarcoma nuclei to deform on micropillar topography. (March 2020) - Tusamda Wakhloo, Nayana; Anders, Sebastian; Badique, Florent; Eichhorn, Melanie; Brigaud, Isabelle; Petithory, Tatiana; Vassaux, Maxime; Milan, Jean-Louis; Freund, Jean-Noël; Rühe, Jürgen; Davidson, Patricia M.; Pieuchot, Laurent; et al.
Abstract: Cell deformation occurs in many critical biological processes, including cell extravasation during immune response and cancer metastasis. These cells deform the nucleus, their largest and stiffest organelle, while passing through narrow constrictions in vivo and the underlying mechanisms still remain elusive. It is unclear which biochemical actors are responsible and whether the nucleus is pushed or pulled (or both) during deformation. Herein we use an easily-tunable poly-L-lactic acid micropillar topography, mimicking in vivo constrictions to determine the mechanisms responsible for nucleus deformation. Using biochemical tools, we determine that actomyosin contractility, vimentin and nucleo-cytoskeletal connections play essential roles in nuclear deformation, but not A-type lamins. We chemically tune the adhesiveness of the micropillars to show that pulling forces are predominantly responsible for the deformation of the nucleus. We confirm these results using an in silico cell model and propose a comprehensive mechanism for cellular and nuclear deformation during confinement. These results indicate that microstructured biomaterials are extremely versatile tools to understand how forces are exerted in biological systems and can be useful to dissect and mimic complex in vivo behaviour.